Psychological Disorders Found On the Early-Age Married Teenagers Who Are Under 18 - Indra Sulistiawati; Cesa Septiana Pratiwi (Universitas 'Aisyiyah Yogyakarta, 2021)
There are in excess of 700 million women around the world married before 18 years old and there are 250 million women married before 15 years old. The early-age marriage is viewed as contributing variable to psychological trauma that influences mental and physical development. The review utilized the Arsksey and O’Malley method, specifically identifying relevant articles, selecting articles, data mapping, arranging, summing up and reporting results. The result of this review indicated that the early-age marriage has various effects on psychological disorders such as anxiety, stress and depression. However, not all articles explicitly state the psychological effect caused by the early-age marriage. Further study should be conducted to identify the psychological disorders on the early-age marriage.